2009
DOI: 10.21273/hortsci.44.7.1850
|View full text |Cite
|
Sign up to set email alerts
|

Southern Highbush Blueberry Production in High Tunnels: Temperatures, Development, Yield, and Fruit Quality During the Establishment Years

Abstract: Growers interested in producing early, high-quality, southern highbush blueberries (Vaccinium corymbosum L.) in high tunnels face a lack of information regarding appropriate cultural methods. We sought to elucidate the optimal date to close high tunnels to hasten vegetative and reproductive growth of organic southern highbush blueberry cultivars Emerald and Jewel grown in Georgia. The three dates selected to close the high tunnels were 15 Dec., 2 Jan., and 16 Jan. High tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 32 publications
7
41
2
Order By: Relevance
“…Although the high tunnel system gives the grower additional control over the microclimate compared with the field, it is not always possible to maintain optimum daytime (25 to 30°C) or nighttime temperatures (%20°C) for crop growth. Increases in nighttime temperatures in the high tunnel compared with the field were modest as has been seen in other studies (Both et al, 2007;Giacomelli, 2009;Jett et al, 2004;Ogden and van Iersel, 2009;Waterer, 2003). On the coldest evenings, the difference of just a few degrees appeared to provide frost protection to the high tunnel transplants even when temperatures dropped below 0°C in the field.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although the high tunnel system gives the grower additional control over the microclimate compared with the field, it is not always possible to maintain optimum daytime (25 to 30°C) or nighttime temperatures (%20°C) for crop growth. Increases in nighttime temperatures in the high tunnel compared with the field were modest as has been seen in other studies (Both et al, 2007;Giacomelli, 2009;Jett et al, 2004;Ogden and van Iersel, 2009;Waterer, 2003). On the coldest evenings, the difference of just a few degrees appeared to provide frost protection to the high tunnel transplants even when temperatures dropped below 0°C in the field.…”
Section: Discussionsupporting
confidence: 57%
“…This absorption was maximized in our system with the addition of black polypropylene landscape fabric over the soil. Cloud cover on cold evenings may also have reduced the rate of radiative cooling from the high tunnel (Ogden and van Iersel, 2009). The popular 'Cherokee Purple' tomato variety appears to be very susceptible to a number of fruit defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High tunnels are generally unheated, plastic-covered structures with passive ventilation (Lamont et al, 2002). Potential benefits of high tunnels for vegetable and small fruit production include freeze protection, high early yields, protection against some diseases and rain, and efficient fertilizer and water use (Lamont, 2005;Ogden and van Iersel, 2009;Strik, 2012). High tunnels may increase air and soil temperatures in areas of cold weather (Kadir et al, 2006;Reiss et al, 2004).…”
mentioning
confidence: 99%
“…A blueberry production study in Georgia indicated HT closure advanced flower initiation by more than 30 days compared to field controls (Ogden and Iersel 2009). Research on strawberries in northern Utah showed HT production could advance the planting date by four weeks compared with outdoor production (Rowley et al 2010).…”
Section: Introductionmentioning
confidence: 99%